Trade in the Time of the Crusades during the Ayyubid Era - Ahmed, Idris (Humanities Journal of University of Zakho, 2021)
The time of the crusades is considered a communication phase between Muslims and Christians at times of war and peace because the human nature bouod them to fight sometime and make a truce other times where at peace time there was a civilization communication between them widely. It is observed the extent of the development of the Islamic civilization on the super interest of the services which help create the trade exchange in terms of facilities, columns and allot categories of people for the trade services and customs exemptions in addition to the bank services and mint various currencies . They were the most important factories which imposed both parties ( Islamis and Christian ) in Levantine Countries to acquire a big degree of importance for the life of both parties in spite of the military confrontation between them, it is doubtless to say those factories helped a lot at least made the war people busy about their war and the trade people busy about their trade. In this research we talked about trade during the crusades where it is indicated to the contact methods between the above parties in addition to the commercial commoudities exchandises and the trade ways through which the merchandises are delivered between the both sides.